PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LEARNING CYCLE 5E PADA MATERI KINGDOM MONERA KELAS X SMA - Resti Musdalifah; Zulfarina Zulfarina; Wan Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: A research was conducted to develop Learning cycle 5E based Student Worksheets (LKPD) in the material kingdom monera at X grade in Senior High School in the Teacher Training and Education Faculty of the University of Riau from July-December 2019. The research refers to the R & D research approach using the model 4D developed. The research was carried out until the development stage. The research subjects were KD 3.5 and KD.4.5. Data were collected using a validation sheet filled out by 5 validators, the first trial was aimed at 5th semester students as many as 10 students and the second trial was aimed at high school class X students as many as 20 people. The validation results obtained an average score of 3.56 with a very valid category, trials I and trials II obtained an average score of 3.72 and 3.59 with very good categories. Based on the results of the research that has been done, it can be concluded that the Learning Cycle 5E Worksheet based on the kingdom monera class X high school material that has been developed is of very good quality. The quality of this LKPD can be seen based on the quality of the content eligibility aspects, design aspects and pedagogical aspects which are in the very valid category.Key Words: Development, Student Worksheet, Learning Cycle 5E